2000
DOI: 10.1046/j.1440-1746.2000.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vascular endothelial growth factor and its receptor expression in human hepatocellular carcinoma biopsy specimens

Abstract: KDR mRNA is significantly overexpressed in HCC lesions and could be associated with the angiogenesis and tumour growth induced by VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…VEGF mRNA expression was not significantly changed after a short pe- riod of ischemia during surgery (data not shown). Shimamura et al 19 have also reported, using liver biopsy specimens, that there was no difference in VEGF mRNA expression between HCC and nontumorous tissue. VEGF expression has been reported to be induced by inflammatory cytokines by infiltrating lymphocytes, 13 which are often observed in chronic hepatitis and cirrhosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…VEGF mRNA expression was not significantly changed after a short pe- riod of ischemia during surgery (data not shown). Shimamura et al 19 have also reported, using liver biopsy specimens, that there was no difference in VEGF mRNA expression between HCC and nontumorous tissue. VEGF expression has been reported to be induced by inflammatory cytokines by infiltrating lymphocytes, 13 which are often observed in chronic hepatitis and cirrhosis.…”
Section: Discussionmentioning
confidence: 94%
“…[14][15][16][17][18] However, in HCC the importance of VEGF expression and its relationship to clinicopathological features of the tumor are still controversial. Shimamura et al 19 have shown that VEGF expression in HCC was not different from that in the corresponding nontumorous portion of the liver. Moreover, according to the reports of Yamaguchi et al 20 and El-Assal et al, 21 VEGF expression did not correlate with angiogenesis or any clinicopathological features of HCC, suggesting that angiogenesis of HCC may not be controlled by VEGF alone but may be mediated by other angiogenic factors.…”
mentioning
confidence: 96%
“…Overexpression of VEGF may be induced by the hypoxic tumor environment (mediated by hypoxia-inducible factor 2-a), activation of EGF receptor (EGFR) and cyclo-oxygenase-2 signaling (Avila et al, 2006;Bangoura et al, 2007). Increased expression of VEGF and VEGF receptors (VEGFRs; which include VEGFR-1, -2 and -3) has been observed in HCC cell lines and tissues, as well as in the serum of patients with HCC (Shimamura et al, 2000;Ng et al, 2001;Dhar et al, 2002;Poon et al, 2004a). The hepatitis B x antigen has also been associated with the upregulation of VEGFR-3 (Lian et al, 2007).…”
Section: Vegf Receptor Signalingmentioning
confidence: 99%
“…The inflammatory condition via NF-κB signaling pathway boosts VEGF expression that acts not only on the proliferation of endothelial cells in the vasculature but also on the proliferation of cancer cells expressing VEGF-A receptor through downstream Akt/mTOR signaling (221,222). Increased VEGF and VEGF receptors (VEGFRs; which include VEGFR-1, -2 and -3) expression has been observed in HCC cell lines and tissues, as well as in the serum of patients with HCC (223)(224)(225)(226). The hepatitis Bx antigen has also been associated with the up-regulation of VEGFR-3 (227).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%